2016
DOI: 10.1037/ccp0000137
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a family-focused intervention for young drivers with attention-deficit hyperactivity disorder.

Abstract: Objective Teenage drivers diagnosed with attention-deficit/hyperactivity disorder (ADHD) are at significant risk for negative driving outcomes related to morbidity and mortality. However, there are few viable psychosocial treatments for teens with ADHD and none focus on the key functional area of driving. The Supporting the Effective Entry to the Roadway (STEER) program was evaluated in a clinical trial to determine whether it improved family functioning as a proximal outcome and driving behavior as a distal o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 70 publications
(104 reference statements)
2
26
0
Order By: Relevance
“…In contrast, research has demonstrated that psychosocial interventions for ADHD have not addressed driving problems. 26 Our results are in line with previous clinical investigations 13 and one population-based study 17 from Sweden and further extend the previous findings in 3 important ways. First, this study is the initial one to date to clarify the association between ADHD medication use and decreased MVCs in a large sample of women with ADHD, and we found that the association in women was as strong as that in men.…”
Section: Research Original Investigation Medication Use For Adhd and supporting
confidence: 82%
“…In contrast, research has demonstrated that psychosocial interventions for ADHD have not addressed driving problems. 26 Our results are in line with previous clinical investigations 13 and one population-based study 17 from Sweden and further extend the previous findings in 3 important ways. First, this study is the initial one to date to clarify the association between ADHD medication use and decreased MVCs in a large sample of women with ADHD, and we found that the association in women was as strong as that in men.…”
Section: Research Original Investigation Medication Use For Adhd and supporting
confidence: 82%
“…Drivers with ADHD demonstrated significant improvements in driving hazard identification response times following a brief computer-based intervention [95]. Other promising approaches for teen drivers for ADHD specifically include the Supporting the Effective Entry to the Roadway program [96,97], which involved driver monitoring using on-board diagnostics coupled with symptom tracking and pharmaceutical interventions which are commonly prescribed to teenagers with ADHD [98].…”
Section: Psychologicalmentioning
confidence: 99%
“…The most comprehensive study to date that has used a driving simulator as part of an intervention for disadvantaged groups was by Fabiano et al (2016). This was an experimental study with participants diagnosed with ADHD randomly assigned to one of two different treatment groups (there was no control group).…”
Section: Interventions Incorporating Simulatorsmentioning
confidence: 99%
“…All of the studies exposed participants to the simulator in small numbers or individual sessions with the exception of the most recent study by Fabiano et al (2016). This approach allows each participant individual time with the simulator.…”
Section: Interventions Incorporating Simulatorsmentioning
confidence: 99%
See 1 more Smart Citation